Cote d'Ivoire : Request for Emergency Post -Conflict Assistance; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2008)
The economic recovery in Cote d'Ivoire is crucial to growth throughout the subregion. The fiscal results and mobilized domestic financing enabled the authorities to make payments to the World Bank and AfDB and reduce domestic arrears. Reporting on quasi-fiscal cocoa levies has improved. Energy sector audits are being finalized, and reporting on financial flows has improved. In view of the efforts made at both political and economic management fronts, authorities appreciated the Executive Board's support for an additional assistance under the IMF's Emergency Post-Conflict Assistance (EPCA) program.